Potret Perempuan Cendekia: Telaah Biografi Zubaidah Binti Ja'far - Baihaqi, Ahmad; Fikrul ‘ilmi Nafi’uddin; Abdulloh Waqi’; Azah Zakiyatul Miskiyah (AL-MUTSLA, 2025)
This study aims to reveal the figure of Zubaidah bint Ja'far as an intellectual woman during the Abbasid Dynasty through a biographical study using library research methods. Data was obtained from classical history books, Abbasid biographies, scientific journals, and related literature, then analyzed through the stages of editing, organizing, and content analysis to obtain a comprehensive picture of her life, role, and contributions. The results of the study show that Zubaidah was shaped by an intellectual family environment and palace literacy traditions that gave her intelligence, leadership, and a strong social vision. Her contributions were evident through the construction of Darb Zubaidah, the provision of water facilities in Mecca, her patronage of scholars and scientific assemblies, and her involvement in palace politics, including her role in the succession of the caliphate. She is an example that women during the golden age of the Abbasids were able to exert significant influence through philanthropy, social policy, and support for intellectual development. This study concludes that Zubaidah bint Ja'far was a visionary female figure whose contributions had a long-term impact on Islamic civilization. Her values of leadership, social concern, integrity, and commitment to the public good remain relevant to be adapted in the context of current women's development and empowerment.